Surat Perjanjian dan Relasi Kuasa dalam Naskah Peti Kesultanan Ternate 113 A 1/22 - Ghozali, Ahmad Sulthon; Christomy, Tommy (Masyarakat Pernaskahan Nusantara, 2023)
This study analyzes the crate manuscript of 113 A 22/1, one of the collections from Sultan Ternate's archive which contains an agreement with the Dutch colonial government regarding the transfer of 150 Ternate soldiers as reinforcements in 1805. the text frames various ideas around power relations. The research was carried out using a qualitative approach with descriptive methods and data collection through literature study. After the philological stage was carried out to open the contents of the manuscript, the theory of critical discourse analysis (CDA) from Van Dijk and the theory of power from Foucauldian perspective were used in the analysis. The results of this study reveal the existence of the idea of power relations which are built at the micro level in the form of discursive devices (consensus, rhetorical devices, and lexicalization), the superstructure level around the structure of treaty letters, and the macro level around colonial-colonized ideas and the idea of governmentality that has been passing down to local authorities. === Penelitian ini menganalisis naskah peti 113 A 1/22, salah satu koleksi arsip Sultan Ternate yang berisi perjanjian dengan pemerintah kolonial Belanda terkait pemindahan 150 prajurit Ternate sebagai bala bantuan pada tahun 1805. Penelitian dilakukan dengan pendekatan secara kualitatif dengan metode deskriptif dan pengumpulan data melalui studi pustaka. Setelah dilakukan tahap filologi untuk membuka isi naskah, teori Critical Discourse Analysis (CDA) dari Van Dijk dan teori kuasa dari perspektif Foucault digunakan sebagai teori dan metode dalam analisis. Hasil penelitian ini mengungkapkan adanya gagasan relasi kuasa yang dibangun dalam level mikro berupa sarana diskursif (konsensus, sarana retorik, dan leksikalisasi), level superstruktur seputar struktur surat perjanjian, dan level makro seputar gagasan penjajah-terjajah dan gagasan mentalitas kepengaturan yang diturunkan ke penguasa lokal.